Presentation of polysomnogram by color voltage array - Pracki, Tadeusz; Wiłkość, Monika; Pracka, Daria (Medical and Biological Sciences, 2014)
The paper contains a description of the original technique known as the Color Voltage Array (CVA) used for graphic presentation of EEG signal for both polysomnographic and EEG research. CVA uses color to present electrical voltages of particular waves in the EEG recordings calculated through the Fast Fourier Transform (FFT). The overnight sleep records of 56 healthy volunteers of both sexes (42 women, 14 men; aged 19-27) were analyzed in order to verify the CVA technique. The obtained results confirm the applicability of the CVA technique to the analysis of the human sleep. For analysis of the sleep process, the authors suggest using the Color Voltage Array technique together with a traditional hypnogram. The informative value of a hypnogram increases significantly when combined with CVA.